Stop thinking about tomorrow: Even in the era of COVID-19 History is teaching past and present : Reflections on teaching History during COVID-19 (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The rapid spread of the COVID-19 pandemic in 2020 has caused a crisis in education, with the digital divide becoming ever more prevalent in a society which is as unequal and fractured as South Africa. While exModel C and private schools made the transition onto online learning with comparative ease at the beginning of the first lockdown, the majority of students and teachers in South Africa were, and continue to be, faced with a lack of internet access and resources to allow for the continuation of teaching and learning. While headlines celebrated a ‘21st century revolution in education’ – essentially undermining the professionalism of teachers and calling into question the value of face-to-face interaction – the oft-neglected global majority continued to be marginalised. This is not to denigrate the innovative methods which teachers in both underprivileged and privileged settings have adopted in the face of the crisis, which range from compressing videos and sending notes via Whatsapp to spending hours on screen teaching synchronous lessons, but rather to highlight the challenges which deserve greater focus in the contemporary socioeconomic milieu. For a subject such as History, this is an opportune moment not only to draw parallels to events such as the Spanish Flu (which too demanded the wearing of protective masks), but also to highlight issues of social justice which are emerging on both a local and global scale.
Keywords: Online learning; COVID-19; History education; Education inequality; Fourth Industrial Revolution; Social justice